A NOVEL LINK BETWEEN ADIPOKINES AND LIPOPROTEIN (A) TO CONTEMPLATE THEIR DIAGNOSTIC ROLE IN PATIENTS WITH STEMI AND NSTEMI - Rashid, Shazia; Khurshid, Rukhshan; Amir, Uzma Faryal; Malik, Arif; Qazi, Sumera (Journal of Ayub Medical College Abbottabad, 2017)
Background: Early detection of cardiac events allow better and cost-effective triage and well-timed management of these patients. Study was conducted to evaluate the prognostic significance of plasma adiponectin, resistin and lipoprotein (a) in a group of patients with ST segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction. These parameters were also compared with other predictors like troponin T, troponin I and CK-MB. Methods: Present study was based on the 100 patients with AMI of whom 52 had a diagnosis of STEMI, and 48 had NSTEMI. Duration of study was January to June 2015. Patients having chest pain that was indicative of myocardial ischemia within first 12 hours after the onset of symptoms were included in the study. Adiponectin, Lp (a), resistin, troponin T and troponin I were estimated using ELISA method. Level of CK-MB was measured by Auto-analyser using standard kit of Merck. Results: Mean age of patients with STEMI was 52.32 years and with NSTEMI it was 48.17 years. Mean value of BMI of patients with STEMI was 28.33 and with NSTEMI was 25.22 Kg/m2. Duration of chest pain in patients with STEMI was 8.64 and patients with NSTEMI it was 16.52hours with highly significant difference (p<0.001). History of smoking in patients with STEMI was more as compared to the patients with NSTEMI. Level of CPK, adiponectin and lipoprotein (a) was raised in patients with STEMI as compared to patients with NSTEMI but significant difference was only found in levels of CPK (p<0.001) and in adiponectin (p<0.05). Level of serum CK-MB, TnT, TnI and resistin was raised in patients with NSTEMI as compared to patients with STEMI but significant difference (p<0.001) was only observed in serum troponin I concentration. Conclusion: It is concluded that the incidence of STEMI and NSTEMI is similar in our patients. However, the markers of STEMI are increased level of adiponectin and Lp(a) and the markers of NSTEMI are troponins especially troponin I, resistin and CKMB. Keywords: Cardiac markers; STEMI; NSTEMI, Adipokines, Lipoprotein